2020
DOI: 10.1155/2020/1929565
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Improving 18F-Fluciclovine PET/CT Reports: A Guide for Physicians Treating Patients with Biochemical Recurrence of Prostate Cancer

Abstract: The positron emission tomography (PET) tracer 18F-fluciclovine has seen increasing use to localize disease in men with biochemical recurrence of prostate cancer, i.e., elevated prostate-specific antigen (PSA) levels post-treatment. 18F-Fluciclovine PET/computed tomography (CT) imaging reports now play central roles in many physician-patient discussions. However, because no standardized grading system or templates yet exist for 18F-fluciclovine image assessment, reports vary in format, comprehensiveness, and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This is evidenced by only 9 out of 321 trials assessed being deemed suitable for inclusion. As previously reported, 18 F-fluciclovine detection rates may differ between centers, possibly due differences in acquisition protocols, scanner type, and/or readers' experience levels [21,22]. It may be that unfamiliarity with 18 Ffluciclovine reporting influenced results, but it has been shown that following limited specific training, naïve readers are able to read 18 F-fluciclovine images with good agreement [23].…”
Section: Post-scan Management Changesmentioning
confidence: 83%
“…This is evidenced by only 9 out of 321 trials assessed being deemed suitable for inclusion. As previously reported, 18 F-fluciclovine detection rates may differ between centers, possibly due differences in acquisition protocols, scanner type, and/or readers' experience levels [21,22]. It may be that unfamiliarity with 18 Ffluciclovine reporting influenced results, but it has been shown that following limited specific training, naïve readers are able to read 18 F-fluciclovine images with good agreement [23].…”
Section: Post-scan Management Changesmentioning
confidence: 83%
“…Since the approval of the F18-fluciclovine radiotracer by the United States FDA in May of 2016, the F18-fluciclovine PET/CT has become an increasingly popular tool used by providers to assess for prostate cancer recurrence [8,16]. It has been shown that the inclusion of F18-fluciclovine PET/CT into postprostatectomy radiotherapy decision-making and planning significantly improved survival free from biochemical recurrence or persistence [9,10].…”
Section: Discussionmentioning
confidence: 99%